INOVASI MESIN PENCINCANG PAKAN TERNAK UNTUK SAPI POTONG PADA KELOMPOK TERNAK GALANGGANG RAYA FARM DI KECAMATAN TANJUNG HARAPAN KOTA SOLOK - Susanti, Oknovia; Ghifary, Muhammad Ghazi Al Ghifary; Fauza, Ahmad Hadi; Yulinda, Yulinda; Arlina, Firda (Jurnal Hilirisasi IPTEKS, 2025)
The Galanggang Raya Farm livestock group in Nan Balimo Village, Tanjung Harapan District, Solok City, faces a major problem in that there are no grass choppers available to support the feed needs of goats and cattle. This problem has resulted in low feed processing efficiency, a high workload for farmers, and limited availability of quality feed. To address this, this community service activity focuses on technological innovation in the form of designing a grass chopper machine that utilizes local resources, both in terms of materials and technical expertise. The primary objective of this community service activity is to enhance the efficiency and sustainability of cattle and goat farming systems by providing a grass chopper machine capable of producing feed cuts of uniform size, thereby supporting improved feed consumption and optimal livestock growth. Additionally, the use of local components aims to reduce production costs, strengthen the local supply chain, and create new job opportunities in the surrounding farming community. The results of this activity demonstrate that the designed grass chopper machine can produce feed pieces of uniform size, in line with the desired specifications. Feed of uniform size has been proven to increase feed consumption by livestock and positively impact the growth of beef cattle. This innovation not only provides a practical and efficient solution for feed processing but also promotes local economic growth through the use of appropriate technology, strengthening farmers' capacity, and improving farm productivity.